The Economy of Promises : Trust, Power, and Credit in America - Carruthers, Bruce G. (Princeton : Princeton University Press, 2022)
A comprehensive and illuminating account of the history of credit in America--and how it continues to divide the haves from the have-notsThe Economy of Promises is a far-reaching study of credit in nineteenth- and twentieth-century America. Synthesizing and surveying economic and social history, Bruce Carruthers examines how issues of trust stitch together the modern U.S. economy. In the case of credit, that trust involves a commitment by debtors to repay money they have borrowed from lenders. Each promise poses a fundamental question: why does the lender trust the borrower?The book tracks the dramatic shift from personal qualitative judgments to the impersonal quantitative measurements of credit scores and ratings, which make lending on a much greater scale possible. It discusses how lending is shaped by the shadow of failure, and the possibility that borrowers will break their promises and fail to repay their debts. It reveals how credit markets have been shaped by public policy, regulatory changes, and various political factors. And, crucially, it explains how credit interacts with economic inequality, contributing to vast and enduring racial and gender differences--which are only exacerbated by the widespread use of credit scores and ratings for "big data" and algorithmic decision-making. Bringing to life the complicated and abstract terrain of human interaction we call the economy, The Economy of Promises is an important study of the tangle of indebtedness that, for better or worse, shapes and defines American lives
Cover -- Contents -- Acknowledgments -- 1. Introduction -- 2. Trust and Credit -- 3. Trade Credit and the Invention of Ratings -- 4. Bank Lending -- 5. Individual and Consumer Credit -- 6. Corporate Finance and Credit Ratings -- 7. Mortgages and Real Estate -- 8. Broken Promises -- 9. Sovereign Borrowers -- 10. Conclusion -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 26, 2022).
JSTOR
Keywords: Credit -- United States -- History; Trust -- United States; Crédit -- États-Unis -- Histoire; Confiance -- États-Unis.; SOCIAL SCIENCE -- Sociology -- General; Credit; Trust; United States; Asset; Bank charge; Bank; Bond (finance); Business model; Capital adequacy ratio; Capital employed; Capital expenditure; Capital intensity; Cash crop; Cash flow; Commerce Clause; Commercial Credit; Commodity market; Commodity; Competition (economics); Consumerism; Credit (finance); Credit Insurance; Credit risk; Creditor; Crony capitalism; Currency; Current Price; Debt limit; Debt; Debtor; Diversification (finance); Economic Life; Economic development; Economic forecasting; Economic indicator; Economic interventionism; Economic policy; Economic sector; Economics; Economy of the United States; Economy; Employment; Exchange rate; Fee Income; Financial capital; Financial inclusion; Financial institution; Financial instrument; Financial intermediary; Financial services; Financial statement; Financial technology; Financier; Floating interest rate; Gross (economics)